Metabolic Alteration in Plasma and Biopsies From Patients With IBD. Issue 8 (29th January 2021) - Santoru, Maria Laura; Piras, Cristina; Murgia, Federica; Leoni, Vera Piera; Spada, Martina; Murgia, Antonio; Liggi, Sonia; Lai, Maria Antonia; Usai, Paolo; Caboni, Pierluigi; Manzin, Aldo; Atzori, Luigi
Abstract: Background: Inflammatory bowel diseases (IBD) are chronic inflammatory disorders of the gastrointestinal tract, with periods of latency alternating with phases of exacerbation, and include 2 forms: Crohn disease (CD) and ulcerative colitis (UC). Although the etiology of IBD is still unclear, the identification and understanding of pathophysiological mechanisms underlying IBD could reveal newly targeted intestinal alterations and determine therapeutic approaches. Methods: In this study, by using gas chromatography-mass spectrometry, we characterized plasma and biopsies from the metabolomics profiles of patients with IBD compared with those of a control group. Results: The results showed a different metabolomics profile between patients with CD (n = 50) and patients with UC (n = 82) compared with the control group (n = 51). Multivariate statistical analysis of the identified metabolites in CD and UC showed changes in energetic metabolism, and lactic acid and ornithine in particular were altered in both plasma and colon biopsies. Moreover, metabolic changes were evidenced between the normal ileum and colon tissues. These differences disappeared when we compared the inflamed ileum and colon tissues, suggesting a common metabolism. Conclusions: This study showed how the metabolomics profile could be a potential tool to identify intestinal alterations associated with IBD and may have application in precision medicine and for better defining the pathogenesis of the disease.